Organisasi pembelajaran : kajian berhubung dengan latihan dalam organisasi yang membentuk ke arah pekerja ilmuan (K-workers)di kalangan pekerja CMS Cement Sdn. Bhd., Kuching Sarawak - Diana, anak David Itang. (Universiti Malaysia Sarawak (UNIMAS), 2003)
(imeral/y. this project aims to peiform a preliminary investigation into the training in developing Dowledge workers among the employees. The knowledge workers are defined as the employees that have wide knowledge. skill/III. creative and innovative. good altitude and responsive. In the histDlY perspective. 1M concept ofknowledge has been started since the industrial revolution in Britain. On that time. there en many manufactories developed. Therefore. they have to compete between each other. The way they QJII solve this problem by training their workers to be more skillful. The skillful workers will help them to N more effective and competitive. After that. the concept ofknowledge workers has been spreaded over tile world and it became a trend in many countries including Malaysia. Nowadays. the concept of knowledge workers is more useful to face the technologies era. Generally. training in the organization is OM ofthe learning processes to design the altitude. skill and knowledge among the employees. so that they CtUI improve their performance in the workplace. In this study. training is divided into two. on-the job lnIining and ofl-the job training. Job instruction training. job rotations and coaching are three types of tnJining which under on-the job training. Besides. there are also three types oftraining techniques under oJI-the job training: lecturing. workshop and computer-based training. The findings ofthis study shows thIlI there is a significant relationship between job insln/ction training. job rotations. coaching and computer-based training with the concept 0/knowledge workers. This is because a/these types o/training tire enjoyable and easy to understand among the employees. Besides. there are two types o/training that do not have significant relationship with the concept 0/ knowledge workers. There are lecturing and workshop. The contents o/these training are unexciting and hard to be understood due to the contents 0/ tile training. In conelusion. not all trainings given in the organization could help in developing knowledge worlcers among the employees.